Anwendungen des positiven Myons als Sonde in der Radikalchemie am Beispiel des Cyclohexadienyl-Radikals - Emil Roduner (CHIMIA)
What is a short-lived elementary particle good for in chemistry? A lifetime of two microseconds does not allow the production of bottles of new compounds. However, it is more than wishful thinking that in 10-10 seconds a positive muon can be substituted in organic free radicals where it plays the role of a proton and serves as an excellent probe to study structure and behaviour of the radical. Using cyclohexadienyl as a selected example it is shown how experiments with muons are conducted and what information of chemical interest is retrieved.